Impact of Ancestral Differences and Reassessment of the Classification of Previously Reported Pathogenic Variants in Patients With Brugada Syndrome in the Genomic Era: A SADS-TW BrS Registry - Chen, Ching-Yu Julius; Lu, Tzu-Pin; Lin, Lian-Yu; Liu, Yen-Bin; Ho, Li-Ting; Huang, Hui-Chun; Lai, Ling-Ping; Hwang, Juey-Jen; Yeh, Shih-Fan Sherri; Wu, Cho-Kai; Juang, Jyh-Ming Jimmy; Antzelevitch, Charles (Frontiers in Genetics, 2019)
Brugada syndrome (BrS) is a heritable disease that results in sudden cardiac death. In the exome/genomic era, certain reported pathogenic variants in some genetic diseases have been reclassified as benign owing to their high frequency in some ancestries. In the present study, we comprehensively reassessed all previously reported pathogenic variants of BrS. We collected all pathogenic variants of BrS reported in the Human Gene Mutation Database and ClinVar throughout April 2017. We compared the minor allele frequency (MAF) of each variant among different ancestries by searching public whole-genome and exome databases. After considering the maximum credible allele frequency, variants with a MAF ≥0.001 were considered to be of questionable pathogenicity. We also investigated the percentage of SCN5A variants with a MAF ≥0.001 in 124 BrS patients from the Han Chinese population. We collected a total of 440 BrS variants, of which 18 had a MAF ≥0.001. There was a greater percentage of non-SCN5A variants with a MAF ≥0.001 than of SCN5A variants (21.8 versus 1.6%, p<0.0001). There were fewer frameshift and nonsense mutations than missense mutations (0.9 versus 5.6%, p=0.032). Of the 18 variants, only 14 (77.8%) were present in the Asian population. In our cohort, we identified two SCN5A variants (p.A226V and p.V1340I) with MAFs ≥0.001 (0.45%). In conclusion, ancestral differences are important when considering the pathogenicity of BrS variants, especially in the case of missense variants and non-SCN5A variants, which may be pathogenic in some ancestries but only disease-predisposing in others.